Drawing therapy based on embodied cognition theory on emotional expression and social behavior in students with autism: a mixed-methods study - Li, Guanghui; Wei, Daren; Xing, Yalong; Li, Yan; Song, Wu (Frontiers in Psychology, 2025)
ObjectiveAutism spectrum disorder (ASD) is often characterized by deficits in emotional expression and social functioning. Existing interventions tend to emphasize behavioral correction, often overlooking the role of bodily movement in cognitive reconstruction and neglecting the emotional-metaphorical function of cultural symbols that may limit therapeutic effectiveness.MethodsThis mixed-method study randomly assigned 60 ASD students aged 6–19 into an intervention group (n = 30) and a control group (n = 30), which received a 9-week Embodied Cognition-Based Drawing Therapy (EC-DT), or a control group (n = 30) that continued routine training. Assessment tools included psychiatric diagnostic instruments, art-based drawing evaluations, and self-report scales (TSCS, GQOL-74). To complement the quantitative results, qualitative data were collected through semi-structured interviews and analysis of participants’ drawings, enabling a case-based evaluation of the intervention’s effectiveness.ResultsQuantitative analyses revealed that the intervention group showed significantly greater improvements than the control group in self-concept (ΔTSCS = 29.37, p < 0.001), social functioning (ΔGAS = 15.6, p = 0.003), and quality of life (ΔGQOL-74 = 21.3, p < 0.001). Qualitative findings identified a “body–media–emotion” pathway, illustrating how participants regulated emotions through tactile engagement (e.g., “feeling emotions flow through the fingertips while drawing circles”) and embedded cultural elements (e.g., using red to symbolize warmth) to enhance emotional resonance and social connectivity.ConclusionThe EC-DT model significantly improves emotional expression, social behavior, and self-concept among autistic students through multisensory integration and culturally embedded embodied experiences. These findings support the development of localized, culturally responsive intervention frameworks. Further longitudinal research is needed to confirm the durability of these therapeutic effects.